Privacy concerns in smart home environment - Mohamed Yusoff, Zuryati; Yeon, Asmah Laili; Mahdzir, Nazli; Basarudin, Noor Ashikin; Md Dahlan, Nuarrual Hilal (2017)
Purpose - Smart home (SH) in Malaysia is still new, yet the application of full SH is growing very fast among home owners in Malaysia. The installation of SH gadgets and facilities is on the choice of the home proprietors themselves. To have better security and comfort of their homes, they improvise the existing features with SH facilities either through hiring contractors fitting the facilities or they install it themselves (DIY).According to research, currently in Malaysia there are only three main standardized technologies having achieved significant deployment as SH facilities; X-10 (a protocol for communication among electronic devices used for home automation), CEBus (short for Consumer Electronics Bus, also known as EIA-600, is a set of electrical standards and communication protocols for electronic devices to transmit commands and data) and Lon Works (a networking platform specifically created to address the needs of control applications), with X-10 being the most widely deployed for home automation (Smart Home Concept, 2003).In years to come, the application of full SH will be widespread at par with the advancement of technology. However, the application and installation of all these gadgets and products entail personal data issues and involve a lot of privacy concerns.Thus, this paper examines those concerns and suggests ways to safeguard privacy of smart home owners.